AN ANALYSIS OF PARAPHRASING TECHNIQUES BY STUDENTS IN WRITING A RESEARCH PROPOSAL TASK IN FIFTH SEMESTER STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM OF THE UNIVERSITY MUHAMMADIYAH KOTABUMI 2023/2024 - Monica Nabila Krisma; Elis Susanti; Desty Fatmawati; Mira Zentia; Gus Haryati; Ranah; Desma Wati (Universitas Muhammadiyah Kotabumi, 2023)
There are many techniques to avoid plagiarism in academic writing, paraphrasing is the most important one. Students often struggle with paraphrasing their quotations correctly and effectively. Furthermore, to overcome this challenge it is important for students to apply some paraphrasing techniques in their writing. The purpose of this study is to describe the paraphrasing techniques used by students and the most dominant techniques used in students' research proposal assignments. This study uses qualitative research that examines 58 paraphrases from 8 research proposal assignments of fifth semester students of English Education Study Program, Muhammadiyah University of Kotabumi. The category of paraphrasing techniques from Bailey 2015 is used in this study as well as the instrument to collect data. The instrument used is document analysis. Data analysis is carried out in several stages: collecting data, identifying data, finding the original source of data, comparing the original source and paraphrase, analyzing data, and interpreting data. The findings show that there are three paraphrasing techniques applied in students' research proposal assignments. Those three techniques are changing vocabulary with synonyms, changing the word class, Changing the word order. Researchers also found that the most dominant technique used by students in writing research proposals was changing vocabulary with synonyms. The paraphrasing technique can be effectively utilized in academic writing, particularly by students, as it allows for the avoidance of plagiarism while simultaneously encouraging the development of original ideas. Considering that this study only focuses on paraphrasing techniques without examining potential errors, future research is suggested to investigate various forms of errors in paraphrasing, not only in surface structure but also in the paraphrasing strategies used.